Analisis metode pencatatan dan penilaian persediaan berdasarkan PSAK 14 pada PT. Hasjrat Abadi Manado - Simatupang, Yulindah Roma Parsaulian; Saerang, David Paul Elia; Lambey , Robert (Manajemen Bisnis dan Keuangan Korporat, 2025)
Inventory plays a strategic role as a current asset in trading companies, particularly in the automotive sector where products have high value and are prone to slow turnover. This study aims to analyze the methods of recording and valuation of car inventory at PT. Hasjrat Abadi Manado and to evaluate their compliance with PSAK 14. The research employs a qualitative approach with a case study design. Data were collected through observations, semi-structured interviews, and documentation, and analyzed using descriptive qualitative techniques by comparing company practices with the provisions of PSAK 14. The results show that the company has implemented a perpetual inventory recording method supported by a computerized Dealer Management System (DMS), which is consistent with PSAK 14. In addition, the valuation of car inventory uses the specific identification method, which is appropriate given the unique characteristics of each vehicle unit. However, the study finds that the company has not recognized impairment for slow-moving car inventory, even though its net realizable value has declined due to significant sales discounts. This practice is not fully in accordance with the lower of cost or net realizable value principle as required by PSAK 14. These findings highlight the need for improved inventory valuation policies to enhance the reliability of financial reporting.